Sulforaphane Wrapped in Self-Assembled Nanomicelle Enhances the Effect of Sonodynamic Therapy on Glioma - Yihong Li; Xuejie Yang; Zhen Wei; Heng Niu; Liyang Wu; Caijing Chen; Huina Liu; Ting Cai; Huadong Fan (Pharmaceutics)
Background/Objectives: The two obstacles for treating glioma are the skull and the blood brain–barrier (BBB), the first of which forms a physical shield that increases the difficulties of traditional surgery or radiotherapy, while the latter prevents antitumor drugs reaching tumor sites. To conquer these issues, we take advantage of the high penetrating ability of sonodynamic therapy (SDT), combined with a novel nanocomplex that can easily pass the BBB. Methods: Through ultrasonic polymerization, the amphiphilic peptides (C18GR7RGDS) were self-assembled as a spherical shell encapsulating a sonosensitizer Rose Bengal (RB) and a plant-derived compound, sulforaphane (SFN), to form the nanocomplex SFN@RB@SPM. Results/Conclusions: SFN@RB@SPM can be internalized by the glioma cells through the tumor-targeting motif RGDS (abbreviated for the peptide sequence composed of arginine, glycine, aspartic acid, and serine), and further executes antitumor function during SDT. Also, SFN@RB@SPM could be easily taken up by U87-MG cells and cross the BBB in glioma-bearing mice during SDT. The mechanism investigation revealed that, compared with the SFN-free nanocomplex (RB@SPM), SFN@RB@SPM induced much more apoptosis of U87-MG cells in an ROS-dependent manner through the depletion of glutathione by SFN and the cavitation effect by SDT. In animal experiments, besides a significant reduction in tumor volume and a delay in losing body weight, H&E staining showed a massive infiltration of neutrophils adjacent to the tumor sites, indicating this novel nanocomplex SFN@RB@SPM can synergistically augment SDT efficacy, partially by enhancing the antitumor function of innate immunity.